Some Reflections on Economic Factors in the Political Unification of Nomadic Peoples - Shavkat S. Amonturdiev, (Zien Journals, 2022)
In the article, the author spoke about the theoretical issues of the emergence and spread of the first "political associations" in the nomadic peoples of Central Asia, economic factors, their areas of residence and the direction of migration, economy
Keywords: nomadic peoples of Central Asia; Saks; massagets; nomadic farms